Targeting chemotherapy-induced VEGF up-regulation by VEGF antisense oligonucleotides in HNSCC cell lines - Riedel, Frank; Götte, Karl; Gößler, Ulrich; Sadick, Haneen; Hörmann, Karl (Anticancer research, 2004)
BACKGROUND: Angiogenesis is increased in various human cancers, including head and neck squamous cell carcinoma (HNSCC), and correlates with tumour progression and metastasis. Vascular endothelial growth factor (VEGF) has been shown to be a key regulator of angiogenesis. Tumour treatment with anticancer agents might have an effect on the secretion of VEGF. Therefore, we determined whether certain chemotherapeutic agents stimulate VEGF secretion in HNSCC and whether VEGF antisense oligonucleotide treatment can modulate these effects in vitro. - MATERIALS AND METHODS: The effect of chemotherapeutic agents (Cisplatin, Carboplatin and 5-FU) on the production of VEGF was investigated on established human HNSCC cell lines at both mRNA and protein levels. By using a 21-mer VEGF antisense phosphorothioate oligonucleotide targeting the translation start site of human VEGF mRNA, we examined modulation of VEGF expression in cell line supernatants by capture ELISA. - RESULTS: The treatment of HNSCC cell lines with chemotherapeutic agents resulted in a significant induction of VEGF production. Carboplatin most prominently induced the release of VEGF from the tumour cells. VEGF antisense oligonucleotide treatment resulted in a significant reduction of chemotherapy-induced VEGF up-regulation compared to sense control. - CONCLUSION: Induction of VEGF secretion might contribute to the frequently observed drug resistance of HNSCC to chemotherapeutic agents. This molecular effect might be reduced by the use of VEGF antisense oligonucleotides in head and neck cancer therapy.